Evidence for a HeLa cell splicing activity that is necessary for activation of a regulated adenovirus 3' splice site. - Zerivitz, K (1992)
Adenovirus late region 1 pre-mRNA splicing is temporally regulated during a lytic infection at the level of alternative 3' splice site usage to produce two mRNAs; the 52,55K and IIIa mRNAs which utilize the proximal and distal 3' splice sites, respectively. In vivo, the 52,55K mRNA is produced both early and late after infection, while IIIa is produced exclusively late in infection. Uninfected HeLa cell nuclear extracts, prepared with a low salt (0.4-0.5 M) or high salt (0.6 M and higher) wash, differed in their ability to splice 52,55K, IIIa and beta-globin transcripts. 52,55K and beta-globin precursors were spliced with similar efficiency in the low and high salt extract, while the IIIa mRNA was generated only in the high salt extract. Using the beta-globin pre-mRNA, no kinetic differences between the two types of extracts were observed. Nor were there any significant differences in the snRNA composition. The IIIa splicing activity did not appear to correlate with U2AF and pPTB levels. Our results suggest that a cellular trans-acting factor(s), which is required for adenovirus IIIa 3' splice site activation, is solubilized only at high salt concentrations.